SADIQ and the Pet Problem - Nuurali, Siman; Sarkar, Anjan (North Mankato, Minnesota : PICTURE WINDOW BOOKS, 2020)
Sadiq's third grade class decides that they want a classroom pet, and their teacher, Ms. Battersby, is okay with the idea, so the students form a club to decide what kind of pet to get, and to research how to take care of it.
Keywords: Sadiq -- (Fictitious character) -- Juvenile fiction; Pets -- Juvenile fiction; Children of immigrants -- Juvenile fiction; Friendship -- Juvenile fiction; American fiction; Africans -- United States -- Juvenile fiction; Children's stories